2020
DOI: 10.1017/s0007114520004560
|View full text |Cite
|
Sign up to set email alerts
|

Digital food environment during the coronavirus disease 2019 (COVID-19) pandemic in Brazil: an analysis of food advertising in an online food delivery platform

Abstract: Food delivery apps guarantee access to food during the COVID-19 pandemic when commercial establishments are closed and access to food retail is controlled. This study aimed to describe the ads published in a food delivery app in Brazilian capitals, during 13th and 14th week of the pandemic. Data collection occurred on one day of the week and one day of the weekend and during lunch and dinner time. A random sample of 25% of the ads (n=1,754) published in this period was classified in accordance to the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 24 publications
2
60
0
1
Order By: Relevance
“…Of these, nearly half were conducted in the United States of America (USA) (n = 4) ( Adams et al, 2020 , 2021 ; Hammons and Robart, 2021 ; Silva et al, 2021 ), followed by two in Latin America (Brazil, Mexico) ( Gonzalez-Alejo et al, 2020 ; Horta et al, 2021 ), and one each in Africa (Zimbabe) ( Murendo et al, 2021 ), Asia (China) ( Ahmed et al, 2020 ), and the Pacific Islands (Samoa) ( Emiliata et al, 2020 ). The majority of studies reported changes in external food environments, including the natural, built ( Ahmed et al, 2020 ; FAO, 2020 ) and digital ( Horta et al, 2021 ), home food environments ( Adams et al, 2020 , 2021 ; Hammons and Robart, 2021 ), and household and individual-level food acquisition practices ( Emiliata et al, 2020 ; Murendo et al, 2021 ; Silva et al, 2021 ) since the onset of the pandemic, with differences and similarities observed between level of country development, stringency of pandemic-related mitigation strategies, and socio-economic status. The one multi-country study that has been conducted interviewed urban food system stakeholders such as provincial government officers ( FAO, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, nearly half were conducted in the United States of America (USA) (n = 4) ( Adams et al, 2020 , 2021 ; Hammons and Robart, 2021 ; Silva et al, 2021 ), followed by two in Latin America (Brazil, Mexico) ( Gonzalez-Alejo et al, 2020 ; Horta et al, 2021 ), and one each in Africa (Zimbabe) ( Murendo et al, 2021 ), Asia (China) ( Ahmed et al, 2020 ), and the Pacific Islands (Samoa) ( Emiliata et al, 2020 ). The majority of studies reported changes in external food environments, including the natural, built ( Ahmed et al, 2020 ; FAO, 2020 ) and digital ( Horta et al, 2021 ), home food environments ( Adams et al, 2020 , 2021 ; Hammons and Robart, 2021 ), and household and individual-level food acquisition practices ( Emiliata et al, 2020 ; Murendo et al, 2021 ; Silva et al, 2021 ) since the onset of the pandemic, with differences and similarities observed between level of country development, stringency of pandemic-related mitigation strategies, and socio-economic status. The one multi-country study that has been conducted interviewed urban food system stakeholders such as provincial government officers ( FAO, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…There was a 10% increase in the use of delivery apps in Brazil during the pandemic [69], and it is known that these applications are characterized as obesogenic because they offer large amounts of ultra-processed foods rich in sugar and fat [70]. Furthermore, these apps intensified their marketing strategies during the pandemic to encourage consumers to purchase these foods [71], and successfully, since a study conducted in the United States showed that individuals are more motivated to wait, work, and pay more for fast food, sweets, and desserts delivery during the pandemic [72], which in turn also had their consumption increased and associated with EE during the pandemic [42,51].…”
Section: Discussionmentioning
confidence: 99%
“…The third marketing strategy is to install and activate GoFood services to promote and sell products, cooperate with Grab and Gojek services for food delivery, online brochure creation and also provide discounts for GoFood and Shopeefood users, and implement sales on take away, delivery order, pick-up, drive-through and also use online food delivery platform (OFD) while offering special offers (Junus et al, 2020 ;Setyowati & Tutiasri, 2021 ;Al-hakim et al, 2021 ;Sukma, 2021 ;Yilmaz &Şahin, 2021 andHorta et al, 2021). The fourth marketing strategy is to include license number of innovating with various flavor variants, not using harmful and safe to consume materials, and using common hashtags to make customer appeal increase (Astutik et al, 2021 andWhite et al, 2020).…”
Section: Re-filtered By Reading Abstracts and Journals Thoroughlymentioning
confidence: 99%